The impact of corporate bankruptcy laws on entrepreneurship: a focus on the French corporate bankruptcy reform of 2006 - Ceccaldi, Alexis Pierre Philippe (2018)
The purpose of this study is to investigate the potential effect of corporate bankruptcy laws on entrepreneurship. The aim is to understand whether or not the change in corporate bankruptcy laws can stimulate entrepreneurial activity, as well as how entrepreneurs consider corporate insolvency legislation. To answer these questions, the study focuses on the case of France, which implemented a major corporate bankruptcy reform in 2006. France represents a compelling case, as it is the developed economy with the lowest creditor-friendly index score. The potential impact of the reform on French entrepreneurs is assessed on quantitative and qualitative grounds through an explanatory sequential mixed method. The results of our quantitative study suggest that the reform of the corporate insolvency procedures introduced in 2006 by the French government did not have a significant impact on entrepreneurial activity in France. Our qualitative results indicate that this may be due to low awareness of entrepreneurs regarding bankruptcy laws because failure is not the focus of entrepreneurs’ attention. However, it is crucial to note that as many variables come into play when dealing with entrepreneurship, the impact of the reform on entrepreneurship may have been affected by other events not taken into account in that model. In the qualitative part, we interviewed French entrepreneurs active at the time of the reform as well as professionals in charge of assisting entrepreneurs whose firms are in difficulties. We tried to investigate what importance entrepreneurs grant to bankruptcy laws and assess the general awareness of entrepreneurs regarding bankruptcy legislation. We also attempted to assess the impact the reform may have had on them, and how they consider the reform. Our qualitative study suggests low awareness regarding the corporate insolvency legislation among entrepreneurs. Interviewees assessed the reform as progress; the main positive feature was the prevention aspect, which allows entrepreneurs who anticipate difficulties to benefit from special procedures. This study may be of interest to policymakers wishing to develop entrepreneurship as well as to entrepreneurs looking for a better understanding of how the institutions impact on them.